Penerapan Bermain Tembak Ikan untuk Meningkatkan Hasil Belajar Siswa - Hafridarli Hafridarli (Jurnal Pendidikan Teknologi Kejuruan, 2019)
This study aims to determine the increase in throwing learning outcomes through a play approach to students. This Classroom Action Research is qualitative research, which lasts for 2 cycles involving all 40 grade IV students. Data analysis techniques, using the results of observations as well as psychomotor, affective and cognitive assessment instruments. Based on the results obtained, in cycle 1, the average cognitive value of the average student scores 26 out of 30, for affective, the average student is perfect, 20 out of 20, and for psychomotor scores, reaches 37 out of a maximum of 50 points, the average accumulative value for this cycle is 83 from a maximum value of 100, and KKM completeness reaches 72.5%. In cycle 2 there is an increase in cognitive and psychomotor aspects. For the cognitive aspect, the average rose by 1 point to 27. For the affective aspect, because the value was maximal in cycle 1, there was no increase, and survived at an average value of 20. For psychomotor values, the average value also rose 3 points to 40. Of the three aspects such an increase in the average accumulative value of 4 points, which is 87, and KKM completeness also increased from 72.5% to 92.5%. Based on the results above, it can be concluded that the game of shooting fish can improve students' abilities and learning outcomes in throwing basic motion in grade IV SDN 22 Koto Baru Kubung District Solok Regency. The author also makes suggestions to students to be more active in practicing to improve psychomotor abilities, both in Penjasorkes lessons, and in the surrounding environment with games that can trigger motoric development, and for teachers to be more creative and innovative in developing material - material that fits the curriculum, but can provide a new atmosphere, so that students are more enthusiastic in following lesson. Penjasorkes teachers are also advised to be more aware of the physical limits of students, so that they can be more appropriate in developing the material, so that it is in accordance with the abilities of the students.